Tahīah al-Biy'ah al-Lughawīyah lil-Mustawā al-Jāmi'i fī Dhaw' Nazariyat al-Binyūyah al-Sulūkīyah. - Fitriani (ALSINATUNA, 2016)
One of language learning issues in any educational institutions is lack of establishment of the language environment. In fact, based on the theories of second language learning called behaviorism and structuralism theory, language is a skill which takes continuous practice and habituation. It means that the most important factor which influences the success of language learning including Arabic language is the availability of good language environment. Therefore, it is necessary for the Arabic education program to establish an Arabic language environment to support the students in improving their language skills.